Control system improvement of qualified boxers based assessment system change reaction cardiorespiratory during the immediate preparation for competition - S.V. Kiprych (Physical Education of Students)
Purpose : Experimental verification and justification of possible practical applications of the method of assessing changes in the functional state of the boxers, based on heart rate variability and spontaneous breathing. In the future, use the results to improve the management of physical exercise in shock and competitive microcycle. Material : The study involved 12 masters of sport of boxing. Instrument was used Sacra. Results : The analysis of heart rate variability and spontaneous respiration showed individual differences changes centile distribution indicators in the management processes of fatigue - recovery cycle training sessions. Conclusions : The differences in the functional state of the body before exercise, during and between training sessions aftereffect. Showing differences readiness athletes to training sessions, the reaction of the organism to the load activation of redox reactions.